Microbial Nitrogen Cycling Becomes Conservative and Resilient to Long‐Term Warming in High‐Latitude Carbon‐Limited Soils - Ana Leticia Zevenhuizen; Andreas Richter; Lucia Fuchslueger; Judith Prommer; Ivan A. Janssens; Niel Verbrigghe; Josep Peñuelas; Bjarni D. Sigurdsson; Sara Marañón‐Jiménez (Global Change Biology, 2026)
High‐latitude soils are warming rapidly due to climate change, raising concerns about long‐term impacts on nitrogen (N) and carbon (C) cycling. Here, we investigate how decadal soil warming affects microbial N transformations in subarctic grasslands using natural geothermal gradients with soil temperatures ranging from ambient to +12.3°C. Seasonal measurements of N‐pools and gross N transformation rates—including the production and uptake of amino acids, ammonium, and nitrate—were used to characterize microbial responses across warming intensities and time. Warming enhanced microbial turnover of amino acids by accelerating both gross amino acid production and uptake, while net depolymerization remained unchanged. In contrast, ammonium production remained stable, but its microbial uptake increased significantly with temperature. These decoupled responses suggest a microbial shift toward preferential use of organic N sources under warming, likely driven by reduced soil C availability. This strategy provides a dual source of C and N, enabling microbes to sustain high metabolic activity while limiting additional N losses. Supporting this, total soil N stocks declined early in the warming period—by 0.11 tons of nitrogen per hectare per degree Celsius over 5 years—but remained stable thereafter, indicating a transition toward more conservative microbial N cycling. Together, these findings reveal that long‐term warming restructures microbial N use strategies, favoring tight organic N recycling and mineral N conservation. These physiological adjustments may buffer N losses under future warming and should be integrated into models predicting high‐latitude ecosystem responses to climate change.

Contrasting drivers of belowground nitrogen cycling in a montane grassland exposed to a multifactorial global change experiment with elevated CO 2 , warming, and drought - Tania L. Maxwell; Alberto Canarini; Ivana Bogdanovic; Theresa Böckle; Victoria Martin; Lisa Noll; Judith Prommer; Joana Séneca; Eva Simon; Hans‐Peter Piepho; Markus Herndl; Erich M. Pötsch; et al. (Global Change Biology, 2022)
Depolymerization of high‐molecular weight organic nitrogen (N) represents the major bottleneck of soil N cycling and yet is poorly understood compared to the subsequent inorganic N processes. Given the importance of organic N cycling and the rise of global change, we investigated the responses of soil protein depolymerization and microbial amino acid consumption to increased temperature, elevated atmospheric CO 2 , and drought. The study was conducted in a global change facility in a managed montane grassland in Austria, where elevated CO 2 (eCO 2 ) and elevated temperature (eT) were stimulated for 4 years, and were combined with a drought event. Gross protein depolymerization and microbial amino acid consumption rates (alongside with gross organic N mineralization and nitrification) were measured using 15 N isotope pool dilution techniques. Whereas eCO 2 showed no individual effect, eT had distinct effects which were modulated by season, with a negative effect of eT on soil organic N process rates in spring, neutral effects in summer, and positive effects in fall. We attribute this to a combination of changes in substrate availability and seasonal temperature changes. Drought led to a doubling of organic N process rates, which returned to rates found under ambient conditions within 3 months after rewetting. Notably, we observed a shift in the control of soil protein depolymerization, from plant substrate controls under continuous environmental change drivers (eT and eCO 2 ) to controls via microbial turnover and soil organic N availability under the pulse disturbance (drought). To the best of our knowledge, this is the first study which analyzed the individual versus combined effects of multiple global change factors and of seasonality on soil organic N processes and thereby strongly contributes to our understanding of terrestrial N cycling in a future world.

Increased microbial growth, biomass, and turnover drive soil organic carbon accumulation at higher plant diversity - Judith Prommer; Tom W. N. Walker; Wolfgang Wanek; Judith Braun; David Zezula; Yuntao Hu; Florian Hofhansl; Andreas Richter (Global Change Biology, 2020)
Species‐rich plant communities have been shown to be more productive and to exhibit increased long‐term soil organic carbon (SOC) storage. Soil microorganisms are central to the conversion of plant organic matter into SOC, yet the relationship between plant diversity, soil microbial growth, turnover as well as carbon use efficiency (CUE) and SOC accumulation is unknown. As heterotrophic soil microbes are primarily carbon limited, it is important to understand how they respond to increased plant‐derived carbon inputs at higher plant species richness (PSR). We used the long‐term grassland biodiversity experiment in Jena, Germany, to examine how microbial physiology responds to changes in plant diversity and how this affects SOC content. The Jena Experiment considers different numbers of species (1–60), functional groups (1–4) as well as functional identity (small herbs, tall herbs, grasses, and legumes). We found that PSR accelerated microbial growth and turnover and increased microbial biomass and necromass. PSR also accelerated microbial respiration, but this effect was less strong than for microbial growth. In contrast, PSR did not affect microbial CUE or biomass‐specific respiration. Structural equation models revealed that PSR had direct positive effects on root biomass, and thereby on microbial growth and microbial biomass carbon. Finally, PSR increased SOC content via its positive influence on microbial biomass carbon. We suggest that PSR favors faster rates of microbial growth and turnover, likely due to greater plant productivity, resulting in higher amounts of microbial biomass and necromass that translate into the observed increase in SOC. We thus identify the microbial mechanism linking species‐rich plant communities to a carbon cycle process of importance to Earth's climate system.